Analisis Pengaruh Faktor Internal dan Faktor Eksternal Kurs Rupiah Terhadap Dollar - Rimma Pebbi Yulihastuti; Sri Ulfa Sentosa; Ariusni Ariusni (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2019)
This research purpose are to the analyse the influence of long-term and short-term internal factor variables (interest rates of Indonesia Bank and Indonesia national income) and external factor variables ( net exports of Indonesia, US foreign interest rate and US foreign inflation) to the rupiah exchange rate against dollar in Indonesia. Methods that being used are Error Correction Model (ECM), the estimation result show that (1) in short-term interest rates of Indonesia, Indonesian national income and net exports in Indonesia caused shocks to the rupiah exchange rate against the dollar in Indonesia, (2) on the long-term national income of Indonesia, US foreign interest rate, and US foreign inflation has a significant influence on the rupiah exchange rate against the dollar, (3) in the short-term the US foreign interest rate and US foreign inflation does not cause a shock to the rupiah exchange rate against the dollar.